(untitled) (Orfeu, 2023)
This article addresses the paradigms that according to Sassaki (2010), were historically present in the education of people with disabilities – the paradigms of exclusion, institutionalization, integration, and inclusion – and their presence in music education practices. It aims to analyze which inclusion paradigms have been adopted regarding the musical education of people with Autism Spectrum Disorder (ASD), according to pedagogical experiences reports published by the Brazilian Association of Musical Education (ABEM) between 1992 and 2022. Through a systematic review of literature, it was possible to identify, in 18 analyzed articles, the paradigm of institutionalization as predominant. All paradigms were found among the works. There was a low occurrence of actions linked to the inclusion paradigm, which was associated with the lack of teacher training to work with autistic students and the lack of resources, especially human resources, that can support the music teacher.